Development of a High Throughput In Vitro Fecal Fermentation Method to Screen for TMA Production Inhibitors - Iglesias-Carres, Lisard (Curr Dev Nutr, 2021)
OBJECTIVES: Choline is metabolized by gut bacteria to trimethylamine (TMA), which is further metabolized by the host into trimethylamine N-oxide (TMAO). There is significant interest in reducing TMAO formation to reduce atherosclerosis risk. Our objective was to develop an in vitro fermentation methodology to screen for bioactives able to reduce TMA formation. METHODS: Choline (5–100 µM) fermentation was optimized under anaerobic conditions at 37°C with the presence of human fecal slurry (OpenBiome) diluted 1:10 in PBS 1X (5–45%) over 36 h. Common dietary phenolics (gallic acid and chlorogenic acid, 0.1–10 mM) were evaluated as TMA production inhibitors under optimal fermentation conditions. 3,3-dimethyl-1-butanol (DMB, 10 mM) was used as a positive control. TMA and choline levels were monitored and analyzed by UPLC-ESI-MS/MS. Cell density (O.D. at 600 nm) was evaluated to account potential cytotoxicity. RESULTS: TMA kinetic production curves from choline at >25 µM were statistically different from background (no choline added), suggesting its potential to be used to assay inhibition of TMA production. Fecal slurry concentration of 5% did not reach a TMA plateau within 36 h of fermentation, while the kinetics reported by 45% were fast, reaching a plateau at 12 h, suggesting the need for intermediate fecal concentrations. Optimal fermentation conditions were 100 µM choline and 20%. fecal slurry Under those conditions, exogenous choline was consumed within the first 12 h of fermentation, during which TMA formation plateaued. Under optimal conditions plus gallic acid or chlorogenic acid, TMA formation was significantly reduced, reaching 50% of inhibitor-free control at concentrations >5 mM at 8 h. Also, >2 mM reported higher inhibition potential than DMB 10 mM. Of note, no reductions in cell density were reported due to treatment administration, suggesting a lack of cytotoxicity. CONCLUSIONS: Our results suggest that gallic acid and chlorogenic acid are promising compounds for in vivo studies. Moreover, our fermentation method can be used to screen for TMA production inhibitors in a high-throughput fashion. FUNDING SOURCES: Supported by through startup funding from North Carolina State University and the Hatch Program of the National Institute of Food and Agriculture, U.S. Department of Agriculture.